Fenomen społeczno-polityczny Radia Maryja - Madera, Andrzej Józef (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2003)
December 2002 saw the 11th anniversary of the first transmission of Radio Maria from Toruń. It is beyond any doubt that the Radio is an actual phenomenon. Over a decade the station of the Redemptorists’ order has succeeded enormously. The reason for this success is an exceptional and original form of a prayer station that is a magnet for millions of listeners. The programs offered by the station from Toruñ are unique and have no counterpart on the media market. The program of Radio Maria is based on three pillars: prayer, catechism and contacting the audience. Particularly the contact with the listeners was decisive for the profound success of the station. It is the most „live” and „interactive” one in Poland. The station contacts its listeners „not only to exchange thoughts and opinions (which is the idea of the program called »Unfinished Conversations«, the first interactive program in Poland) but also to unite in prayer”.